Polystyrene-diphenyloxazole-chlorin e6 nanosystem for PDT: Energy transfer study. (1st November 2016) - Losytskyy, M. Yu.; Vretik, L. O.; Nikolaeva, O. A.; Marynin, A. I.; Gamaleya, N. F.; Yashchuk, V. M.
ABSTRACT: As the step to design nanosystems for X-ray excited sensitizing of singlet oxygen, nanoparticles of polystyrene and polystyrene with encapsulated 2, 5-diphenyloxazole were synthesized. Binding of the photosensitizer chlorin e6 molecules to both kinds of nanoparticles was shown. Excitation energy transfer from styrene chromophores of polystyrene to the bound chlorin e6 molecules occurs in the case of both kinds of nanoparticles. Efficiency of the energy transfer in 2, 5-diphenyloxazole-mediated case is higher (0.17) as compared to the non-mediated one (0.12).